An Analysis of the Performance, Causes and Propagation Path Optimization of “ Narrative Simplification ” and “ Cultural Misreading” of Tai-Chi Communication from the Perspective of Digital Media - Li, Yiming; Chen, Xinmeng (The Journal of the International Society of Chinese Health Practices, 2025)
Abstract: Science ancient times, China has emphasized the “unity between man and nature, the way of neutralization”. As the living carrier and crystallization of wisdom of Chinese traditional culture, Tai-Chi, its “establishment requires a central and unbiased life, so that it can support it from all sides” is internalized into the Chinese people’s tolerant and humble way of dealing with things, conveying to the world an image of a great nations that pursues harmonious coexistence and harmonious development. However, in the process of development, inheritance and dissemination, it is faced with the dilemma of rigidity in cultural symbols and narrowing connotations, which leads to it being misunderstood as the entertainment of the twilight. Young people are reluctant to do this, and its philosophy of “yin and yang” and “both form and spirit” are obscured by the appearance of “body movement”. Despite the vigorous development of digital communication media, the creative translation of Tai-Chi techniques by short videos, film, television works and games has activated the contemporary vitality of traditional cultural symbols to a certain extent. But the spread of chaos also followed. Therefore, this study aims to focus on sorting out the main narrative strategies of Tai-Chi inheritance and communication in the current mainstream digital media platforms, and analyzing the phenomenon of “narrative simplification” and “cultural misreading” in the short-flat-fast fragmentation communication. Through the mixed research methods such as documentary method, logical analysis method, conceptual analysis method, comparative research method, case study method and theoretical analysis method, comprehensive analysis manifestations of Tai-Chi narrative simplification and the generation and representation of cultural misreading in the digital media perspective. At the same time, the reasons are analyzed from multiple dimensions such as platform recommendation mechanism, communication subject, audience cognition and cultural context. Finally, we take symbolic interaction theory as the core framework, combine media environment science and use-satisfaction theory, this paper explores the optimal path paradigm that takes into account cultural authenticity and communication efficiency, enhances the cultural identity of the audience, and realizes the “living inheritance” of Tai-Chi spread in the perspective of digital media